2014
DOI: 10.1167/iovs.14-15376
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude of Accommodation in Type 1 Diabetes

Abstract: Lowered amplitude of accommodation exists in individuals with type 1 diabetes when compared with age-matched controls. The loss correlated strongly with duration of diabetes. The results suggest that individuals with diabetes will experience presbyopia earlier in life than people without diabetes, mainly due to changes in the lens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 19 publications
4
37
0
Order By: Relevance
“…We have previously demonstrated a lower amplitude of accommodation in people with Type 1 diabetes compared with age‐matched people without diabetes (Fig. ) and also showed that people with diabetes become presbyopic 3 to 5 years earlier .…”
Section: Amplitude Of Accommodationmentioning
confidence: 65%
See 2 more Smart Citations
“…We have previously demonstrated a lower amplitude of accommodation in people with Type 1 diabetes compared with age‐matched people without diabetes (Fig. ) and also showed that people with diabetes become presbyopic 3 to 5 years earlier .…”
Section: Amplitude Of Accommodationmentioning
confidence: 65%
“…A lower amplitude of accommodation can occur in people with, compared to people without diabetes. Indeed diabetes duration is as important as age in reducing the amplitude of accommodation . Mäntyjärvi and Nousiainen studied the subjective amplitude of accommodation in school children with Type 1 diabetes and found ~1.9 D less amplitude of accommodation compared with children without diabetes.…”
Section: Amplitude Of Accommodationmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported ocular biometry and amplitude of accommodation of a group of people with type 1 diabetes (DM1) in comparison with controls [1,2]. Generally, the eyes of people with DM1 behaved liked aged versions of eyes of people without diabetes, although there were no accelerated rates of change of parameters with age compared with the controls.…”
Section: Introductionmentioning
confidence: 99%
“…Stating ''any change in accommodative amplitude induced by gravity is not clinically significant'' is true but not relevant. Also not relevant is the claim about lack of effect of gravity being found in pilots and astronauts-one referenced study did not involve accommodation 3 and two referenced studies involved astronauts 4,5 who, from their ages, would have had real amplitudes less than 4 D. 6 Augousti and Pierscionek argue that the Lenstar repeatability (given as twice the standard deviation of repeated measurements) is bigger than the effects we obtained, referencing the instrument manual as giving a standard deviation for repeatability of 0.04 mm. 7 This is an intrasession repeatability, rather than an intersession repeatability, which is the relevant repeatability when considering whether the effects found by us are real.…”
mentioning
confidence: 99%